3D Printer Based Slot‐Die Coater as a Lab‐to‐Fab Translation Tool for Solution‐Processed Solar Cells. Issue 4 (7th November 2014) - Vak, Doojin; Hwang, Kyeongil; Faulks, Andrew; Jung, Yen‐Sook; Clark, Noel; Kim, Dong‐Yu; Wilson, Gerard J.; Watkins, Scott E.
<x xml:space="preserve">Abstract</x> A 3D printer based slot‐die coater is developed as a lab‐to‐fab translation tool for solution‐processed solar cells. The modified 3D printer is used to develop the printing process for potential use in large scale roll‐to‐roll production. Fabrication of a 47.3 cm2 organic solar cell module with 4.56% efficiency and printed perovskite solar cells with 11.6% efficiency are demonstrated. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>